Globalization, Restructuring and Unions: Transnational Co-ordination and Varieties of Labour Engagement - Pulignano, Valeria; Lucio, Miguel; Walker, Steve (Relations industrielles / Industrial Relations, 2013)
SummaryThis paper considers the various ways in which unions respond to transnational restructuring in their longer-term planning and at different levels of action. To this extent, it avoids simply falling into a workplace-based view of mobilizing, or a national and state level view of union lobbying and mobilizing, but instead looks at how different (multi) levels of union action develop (or otherwise) a portfolio of sustainable longer term planning approaches. More concretely, it examines the way that unions activate their learning capacity at various levels in order to develop and use coordination and networking to respond to transnational restructuring. We approach restructuring not only from the point of view of unions’ external organizational relations (employers, members, community, etc.), but also their internal organizational requirements and relations that build a more proactive union response.To reframe the context in which union coordination capability is built up, transnational restructuring should be examined. We start from a conceptual distinction between “influencing” (external) and “communication” (internal) union strategies. Specifically, four different strategies, which take place at different levels of union action, are identified and presented in the paper. They reflect different dimensions of coordination as a feature of long term union learning and preparation in relation to restructuring: (1) lobbying and campaigning to influence the macro-level regulatory environment; (2) organizing and coordinating action in relation to influencing micro-level change; (3) developing informational and learning strategies about skills and training development to prepare individuals for negotiating change at the micro-level; and (4) developing communication and exchange of information with each other to create greater levels of awareness and focus in relation to restructuring at the macro-level.Conclusions identify that the structure and content of union coordination in the context of cross-border restructuring is a complex issue that cannot be reduced to simple historical binaries of bureaucracy-activist or employer facing versus membership facing. Our findings demonstrate that coordination works across various sets of dimensions (i.e. “influencing” and “communicating”), relations (internal and external) and levels (i.e. micro and macro). Therefore, it requires complex sets of organization and agendas.